2008
DOI: 10.1007/s00418-008-0512-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of both oestrogen receptor alpha and beta in human skeletal muscle tissue

Abstract: There are two oestrogen receptors (ERs), ERalpha and ERbeta. ERbeta protein is expressed in human skeletal muscle in the nuclei of both myofibres and endothelial cells, whether ERalpha protein is present in this tissue is unknown. We studied the expression of ERalpha protein in human skeletal muscle biopsies taken from vastus lateralis from four men, four women, two children and two postmenopausal women. Immunohistochemistry was used to determine the proportions of nuclei that were positively stained for ERalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 45 publications
1
111
1
2
Order By: Relevance
“…Skeletal muscle is expected to be a target tissue for estrogens because two ER isoforms are expressed in skeletal muscle (6). In the present study, E2 induced USP19 expression in vitro and in vivo, and E2-induced USP19 inhibited myogenesis.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Skeletal muscle is expected to be a target tissue for estrogens because two ER isoforms are expressed in skeletal muscle (6). In the present study, E2 induced USP19 expression in vitro and in vivo, and E2-induced USP19 inhibited myogenesis.…”
Section: Discussionmentioning
confidence: 47%
“…For example, ER␣ promotes cell proliferation in the development of the reproductive tract and mammary gland, whereas ER␤ seems to have potent antiproliferative (3,4) and anti-inflammatory properties (5). Recently, ER␣ and ER␤ have been identified in skeletal muscle (6). Therefore, estrogens seem to act on skeletal muscle through ER isoforms.…”
mentioning
confidence: 99%
“…In addition to the study design, methodology and study group, the dose and duration of HRT usage, and the time between menopause and data collection may be very important variables. In this study the self-reported mean time from menopause was 7.0 (range [3][4][5][6][7][8][9][10][11][12][13] years in the non-users and 8.3 (range 3-19) years in the HRT users with mean of 6.8 years (range 2-16) on the treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Especially, the notion that both estrogen receptors are expressed in human skeletal muscle cells of both genders [7][8] , implies that muscle is a target tissue for estrogen signaling. Estrogen has also been suggested to preserve type II muscle fibers in a study performed on ovariectomized rats 9 .…”
Section: Introductionmentioning
confidence: 99%
“…ER␣ and ER␤ have been identified at the protein level by immunohistochemistry and was found to be localized to the nuclei of both muscle fibers and endothelial cells (35)(36)(37). ERs in myoblasts appear to be functional when stimulated with estrogen (20), and estrogen stimulation increases expression of insulin-like growth factor (IGF-1) in both myotubes and proliferating myoblasts (21).…”
mentioning
confidence: 99%